2002
DOI: 10.1074/jbc.m109296200
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Represses Transcription of the IL-1β Gene through Physical Interaction with the Nuclear Factor of Interleukin 6

Abstract: Heat shock factor (HSF) 1 is the major heat shock transcription factor that regulates stress-inducible synthesis of heat shock proteins and is also essential in protection against endotoxic shock. Following our previous study, which demonstrated the transcriptional repression of the IL-1␤ gene by HSF1 (Cahill, C. M., Waterman, W. R., Xie, Y., Auron, P. E., and Calderwood, S. K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 66 publications
8
140
3
Order By: Relevance
“…Similarly, recent studies have reported that HSF1 acts as a transcriptional repressor of certain cytokine genes, including TNF-a and IL-1b, to prevent LPS-induced inflammation. 29,43,44 These results support our findings that HSF1 protects cardiomyocytes via transcriptional repression of IGF-IIR expression. Our results demonstrate that ANG II represses HSF1 by two mechanisms: (1) phosphorylation of HSF1 Ser303 to inhibit its transcriptional activity and (2) acetylation of HSF1 Lys80 to suppress its DNA-binding activity.…”
Section: Ser303supporting
confidence: 81%
“…Similarly, recent studies have reported that HSF1 acts as a transcriptional repressor of certain cytokine genes, including TNF-a and IL-1b, to prevent LPS-induced inflammation. 29,43,44 These results support our findings that HSF1 protects cardiomyocytes via transcriptional repression of IGF-IIR expression. Our results demonstrate that ANG II represses HSF1 by two mechanisms: (1) phosphorylation of HSF1 Ser303 to inhibit its transcriptional activity and (2) acetylation of HSF1 Lys80 to suppress its DNA-binding activity.…”
Section: Ser303supporting
confidence: 81%
“…High levels of calgranulin-S100A8/A9 acted as chemoattractant for leucocytes and as an important regulator of inflammation, whose synthesis is enhanced by IL-17A [39]. The heat shock proteins, HSP-27, HSP-60 and HSP-70, interacted with dendritic cells, monocytes and MSC to induce IL-10 synthesis [42,43]; furthermore, activation of the HSP gene (HSF1) would have repressed transcription of IL-1β in the wound site [44]. In short, we propose that sterile trauma induced a DAMP-driven anti-inflammatory milieu, reinforced by IL-6, IL-9, IL-10, TGF-β and IL-1RA, whose primary function was to suppress activation of tissue damaging inflammatory cascades, while simultaneously facilitating tissue regeneration by inducing the chemokines IL-8/CXCL8, MCP-1/CCL2 and MIP-1α/CCL3.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HSF1 binds the 5'-untranslated region of the murine TNF-α gene to repress transcription (162). In a similar manner, HSF1 represses transcription of the gene for IL-1β through physical interaction with the CCAAT/enhancer binding protein (163).…”
Section: Stress Proteins and Cytoprotectionmentioning
confidence: 99%
“…Recent studies suggest that HSF1 acts directly as a transciptional repressor of several proinflammatory proteins, including IL-1β, c-fos, urokinase, and TNF-α (162,163). For example, HSF1 binds the 5'-untranslated region of the murine TNF-α gene to repress transcription (162).…”
Section: Stress Proteins and Cytoprotectionmentioning
confidence: 99%